THE INFLUENCE OF SAVING PRODUCT ATTRIBUTES AND QUALITY OF SERVICE ON BANK CUSTOMER SATISFACTION - Cholifah Cholifah; Agus Sukoco (Jurnal Ekonomi, 2019)
This study aims to determine the effect of savings products and service quality on customer satisfaction in the workplace. The sample in this study were 100 customers of the PT Bank Jatim Tenggilis Surabaya Branch Office. Data collection techniques in this study were observation, questionnaires, and librarian studies. While the data analysis technique used is the classical assumption test technique, multiple linear regression analysis, and hypothesis testing using SPSS 17 software. The results show that there is an influence between savings products and services on customer satisfaction. There is a positive and significant influence between savings products and services on customer satisfaction, so the hypothesis is accepted. The coefficient of determination is 0.443 which indicates that the savings products and services together can explain the customer satisfaction of the PT Bank Jatim Tenggilis Surabaya Sub-Branch Office by 44.3%, while the rest is influenced by other variables not examined. There is a relationship between savings products and services with customer satisfaction, so companies must pay more attention to the service products sold and the services provided to create customer satisfaction.